Stress analysis of film-on-substrate structure under tensile loads. (May 2018) - Li, Lin-An; Li, Rong-Jian; Wang, Shi-Bin; Wang, Zhi-Yong; Li, Teng; Li, Chuan-Wei
Highlights: A theoretical model was established to precisely describe the total stress distribution of the FOSS under tensile loads. The thickness effect of the film was considered and the. Finite Element Analysis was conducted to validate the theoretical model. Abstract: In this study, the internal stress distribution of a film on substrate structure (FOSS) under tensile loads has been analyzed. Based on force balance principles, analytical solutions are deduced to solve the elastic problem for the FOSS considering the mismatch of mechanical parameters between the film layer and the substrate. The stress distributions of both monolayer FOSS and multilayer FOSS are determined. The effect of the influencing factors such as mechanical parameters and structural thickness on stress distributions are taken into account. From the finite element method (FEM) results presented in this work, the proposed theoretical model is feasible. In addition, the classic shear-lag theory is employed to verify the proposed method. The result indicates that the proposed model has a more extensive applicability for both thin films and thick films.